Areas of geohydrological risk in the urban perimeter of the Municipality of Coluna in the State of Minas Gerais (International Journal of Geoscience, Engineering and Technology, 2025)
This study presents the initial results of the geohydrological risk survey conducted in the Municipality of Coluna, State of Minas Gerais, Brazil. In this matter, field surveys were conducted, integrating with historical records of landslides and floods, which enabled the classification of geohydrological risks from R1 to R4, in accordance with the methodology of the Brazilian Ministry of Cities, as well as an understanding of the region's vulnerability. With unplanned urbanization, human interventions, road construction, and building in unsuitable areas, the risk of environmental disasters is increased in the city of Coluna, characterized by soils susceptible to erosion, irregular topography, and steep slopes, increases during the rainy season. The results obtained at the six points studied, called A, B, C, D, E and F, indicate that the lack of adequate drainage, combined with interventions without technical criteria, increases soil instability and population exposure, with Points A, B, E and F being high risk (R3) and Points C and D being medium risk (R2). It is therefore essential to implement prevention and mitigation strategies, such as rigorous urban planning, inspection, containment and drainage works, and environmental education, as fundamental measures to reduce vulnerabilities, protect lives, and promote safer and more sustainable development in the city of Coluna.